The hypoglycemic effect of ginsenoside Rd in db/db mice is mediated by increased insulin sensitivity and suppressed hepatic gluconeogenesis - Zaiqi Han; Haihui Yu; Zhe Liu; Yue Zhong; Sheng Chang; Xin Sun; Lu Yao (Journal of Functional Foods)
Ginsenoside Rd, one of the major components entering into the circulation from ginseng, is beneficial to health; however, its role and mechanism in improving T2DM require further exploration. In the current study, we explored the hypoglycemic effects of Rd in diabetic db/db mice and examined the underlying mechanisms. The results disclosed that after Rd treatment for four weeks, hyperglycemia, insulin resistance, and pyruvate intolerance were improved; moreover, hepatic steatosis was ameliorated. Additionally, Rd increased the phosphorylated Akt ratio in insulin-regulated peripheral tissues and decreased hepatic gluconeogenic gene expression. In vitro experimental results demonstrated that Rd decreased cellular glucose output from insulin-resistant mouse and human hepatocytes. Rd reduced gluconeogenic gene expression through inhibiting Foxo1 transcriptional activity. Taken together, our results suggest that Rd mitigates hyperglycemia in db/db mice by enhancing insulin sensitivity and diminishing hepatic gluconeogenesis, thus providing a theoretical principle for applying ginseng and ginsenoside Rd on curing T2DM.